2017
DOI: 10.3390/en10111688
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Modelled and Measured Tilted Solar Irradiance for Photovoltaic Applications

Abstract: This work assesses the performance of five transposition models that estimate the global and diffuse solar irradiance on tilted planes based on the global horizontal irradiance. The modelled tilted irradiance values are compared to measured one-minute values from pyranometers and silicon sensors tilted at different angles at Hannover (Germany) and NREL (Golden, CO, USA). It can be recognized that the deviations of the model of Liu and Jordan, Klucher and Perez from the measurements increases as the tilt angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…The isotropic sky model under-predicts total radiation on a tilted surface and is not recommended for general use. The HD and Reindl models were recommended in the mentioned references [25,26]. The HD model has also been selected to predict total tilted solar radiation in Greece [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isotropic sky model under-predicts total radiation on a tilted surface and is not recommended for general use. The HD and Reindl models were recommended in the mentioned references [25,26]. The HD model has also been selected to predict total tilted solar radiation in Greece [45].…”
Section: Discussionmentioning
confidence: 99%
“…Mubarak et al [25] compared five empirical models for PV applications. The authors concluded that the models of Hay and Davies and Reindl are recommended to estimate tilted irradiance for south-facing modules in regions with mainly cloudy conditions and when albedo measurements are not available.…”
Section: State Of the Artmentioning
confidence: 99%
“…A pyranometer is used to measure the irradiance of the sun [3]. It can be installed on a surface to measure the global irradiance received from the hemisphere, as shown in Figure 1 [4][5][6]. It is used to measure global (diffuse and beam) irradiance on a horizontal plane [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…It can be installed on a surface to measure the global irradiance received from the hemisphere, as shown in Figure 1 [4][5][6]. It is used to measure global (diffuse and beam) irradiance on a horizontal plane [3,6]. However, pyranometers have several disadvantages: (1) the price can be between $300 (with low accuracy) and $1800 (with high accuracy), (2) the sensitivity can vary with time, (3) exposure of irradiance with long time and high temperature (>50 °C) can reduce the accuracy of the device, and (4) the pyranometer needs to be calibrated daily and whenever there is a significant variation in weather conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…In our field sites LAI ranged from 0.0-2.1 and was <1 in most sites. In another study, Inge (1968) reported that silicon pyranometers overestimated plant, sand, water, and rock albedo by ∼0.03, and suggested caution should be taken for measuring snow albedo as the overestimation can be as high as 0.09. Stroeve et al (2005) found that silicon pyranometers can overestimate albedo by 0.04-0.09.…”
mentioning
confidence: 99%